Cognitive behaviour hypnotherapy and Nonsuicidal self-injury disorder: intervention study - Qureshi, Halima Sadia; Sadiq, Urooj (Journal of the Pakistan Medical Association, 2022)
Objective: To identify the effect of cognitive behaviour hypnotherapy on nonsuicidal self-injury condition. Methods: The quasi-experimental study was conducted from May 2019 to April 2020 in Islamabad and Rawalpindi, Pakistan, and comprised students aged 18-25 years at various universities and colleges in the twin cities. The participants were screened using deliberate self-harm inventory for >2 events without suicidal intention in line with the Diagnostic and Statistical Manual of Mental Disorders 5th edition. They were then divided into two intervention and control groups. Over the following three months, the intervention group received cognitive behaviour hypnotherapy, while the control group did not receive any treatment. The groups were assessed post-intervention. The final phase comprised follow-up assessment of the condition. Data was analysed using SPSS 25. Results: Of the 60 subjects, there were 30(50%) in each of the two groups. Overall, there were 41(68%) males and 19(32%) females. The majority of the subjects were aged 21-23 years 29(48%). More than 5 self-harm incidents were reported by 48(80%) subjects, while suicidal ideation was detected in 6(10%) students. The effect size of the study was good in terms of pre- and post-intervention values (d=4.90), the post-intervention and follow-up assessment values (d=0.32) and the pre-intervention and follow-up values (d=5.42). The comparison between treatment and no treatment groups indicated the effectiveness of treatment over no-treatment, F (1, 58) = 53.16, p < .001. Conclusion: Cognitive behaviour hypnotherapy was found to be effective in treating the nonsuicidal self-injury condition. Continuous...